Finding Empathy Through Music Therapy Techniques in the Mist of Family Trauma: An Autoethnography - dos Santos, Andeline (Voices: A World Forum for Music Therapy, 2024)
Autoethnography involves rigorously describing personal experience and situating this by standing back, engaging in critique, and suggesting how the insights reached could be helpful to others. The author of this autoethnography (a music therapist and empathy researcher) sought to explore her own personal empathy struggles. A challenge in her family context that evoked experiences related to past trauma invited her into a process using music therapy techniques as she asked: How can the tools developed in her research on empathy help her make sense of this experience? How can these tools awaken more empathic responses to her child? How can going through this process give her greater insight into its potential use within music therapy sessions? By designing a series of experiences using receptive and active techniques, she explored how two empathy pathways (insightful empathy and relational empathy) could assist her in processing her thoughts and feelings as well as engaging in more other-centred empathy towards her child within the family situation of concern. The implications for drawing on such a process within a music therapy context are explored.